2010
DOI: 10.1097/pep.0b013e3181cbf852
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Age and Gender on the Weight and Use of Schoolbags

Abstract: Younger children are in greater need for education about schoolbag weight compared with older ones. There is also evidence that girls might experience more problems when carrying their schoolbag compared with boys.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
55
3
17

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(84 citation statements)
references
References 29 publications
9
55
3
17
Order By: Relevance
“…The duration of schoolbag carrying time was short, and was similar to that reported in the literature on primary school children [4,26,27]. Additionally, longer carrying times have been reported in studies that included secondary school children [23][24][25].…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…The duration of schoolbag carrying time was short, and was similar to that reported in the literature on primary school children [4,26,27]. Additionally, longer carrying times have been reported in studies that included secondary school children [23][24][25].…”
Section: Discussionsupporting
confidence: 62%
“…Schoolbag weight and duration of carriage have been investigated within the same studies, but independent of each other [1,4,24,[26][27][28]. However fundamental biomechanical principles of load and energy consumption suggest that schoolbag weight, and the exposure to that weight, should be investigated in combination with each other in order to acquire a measure of the mechanical burden that results from carrying a schoolbag.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To this end, Paušić et al 9 investigated the weight of schoolbags in students from the 1 st to the 4 th grade and found that the limit of 10% of body weight was exceeded in every grade, with higher excess in the initial ones. This last result was also found by Kellis and Emmanouilidou 13 , who also observed that the weight of schoolbags in relation to body weight is greater for girls than for boys. The authors still observed that younger children more often wear the double-strap-backpack on the shoulders than older children, and that boys wear the backpack in greater proportion than girls.…”
Section: Introductionsupporting
confidence: 73%
“…Use of heavy backpacks and carrying these asymmetrically (16), sitting for long periods of time with poor posture (30), use of anatomically incorrect furniture (18), watching television for long periods of time, performing different ADL with incorrect posture (28), sleeping less than seven hours a day, smoking, obesity (22), and psychological factors such as depression and anxiety (8,18) are some of the risk factors for onset of back pain in students.…”
Section: Introductionmentioning
confidence: 99%